Maternal Mortality and Scheme for a National Maternity Service (interim report) - Labour Party (Great Britain). Advisory Committee on Public Health. Sub-committee on Maternal Mortality
1929-11 1929 1920s 12 pages SCHEME for A NATIONAL MATERNITY SERVICE PART I. National Scheme PART II. Local Schemes PART I NATIONAL SCHEME Introductory 1. In submitting the following scheme, your sub-committee wishes it to be understood that the scheme is in broad outline only, that it is not an ideal or perfect scheme, but that it is one which can be administered by all local authorities, either separately or in groups, under the provisions of the Maternity and Child Welfare Act. Assuming that the full administration of the maternity provisions of this Act becomes compulsory for all local authorities, the practical measures outlined in this scheme involve very little additional legislative action. 2. Your sub-committee realises that a scheme which is to meet the requirements of 62 administrative counties, 83 county boroughs (8 of which contain teaching hospitals), and 29 metropolitan boroughs (apart from the large number of urban districts and the smaller number of rural districts, the councils of which now administer the Maternity and Child Welfare Act and to whom its administration may continue to be delegated) must be capable of adaption and variation. They submit that this scheme fulfils these requirements. Examples of local schemes based upon it will be given in Part II. 292/824/1/115